Mixture-risk-assessment of pesticide residues in retail polyfloral honey. (September 2016) - Juan-Borrás, Marisol; Domenech, Eva; Escriche, Isabel
Abstract: The presence of even tiny quantities of pesticide residues in honey, a traditional healthy product, is a matter of concern for producers, packers and consumers. This paper aims to quantify pesticides in retail brands of polyfloral honey, and to calculate the mixture risk assessment of honey for consumers according to the results obtained from the analysed samples. A LC-MS/MS multi-residue method was developed and validated for 13 compounds: 11 pesticides (chlorfenvinphos, coumaphos, tau-fluvalinate, amitraz, which are very common in veterinary treatments, and imidacloprid, acetamiprid, simazine, cyproconazole, tebuconazole, chlorpiryphos-methyl, chlorpiryphos, widely used in agricultural practices), and 2 metabolites of amitraz (2, 4-DMA and 2, 4-DMF). Results showed that the samples contained pesticide residues at different concentrations; however, the MRL in honey for each of the 11 pesticides was never exceeded. The most common were amitraz (from 1 to 50 μg/kg) present in 100% of the samples, and coumaphos (up to 14 μg/kg) in 63%. The hazard index (HI) for adults was less than 0.002 in all cases, a long way from 1, the value established as the limit of acceptability. Therefore, commercial honey does not represent any significant risk to health. However, considering that residue levels should be present "as low as reasonably achievable" it is deemed necessary to make an effort to reduce their presence by appropriate agricultural and, above all, beekeeping practices due to acaridae treatments. Highlights: The MRL for 11 pesticides in polyfloral honey was not exceeded in any of the cases. The pesticide hazard index in honey was much lower than the acceptable limit. Pesticides in commercial honey are not a significant risk to health.